The misadventures of Maude March, or, Trouble rides a fast horse - Couloumbis, Audrey (Random House, 2005)
After the death of the stern aunt who raised them since they were orphaned, eleven-year-old Sallie and her fifteen-year-old sister escape their self-serving guardians and begin an adventure resembling those in the dime novels Sallie loves to read.